2012
DOI: 10.1371/journal.pone.0038865
|View full text |Cite
|
Sign up to set email alerts
|

When Cytokinin, a Plant Hormone, Meets the Adenosine A2A Receptor: A Novel Neuroprotectant and Lead for Treating Neurodegenerative Disorders?

Abstract: It is well known that cytokinins are a class of phytohormones that promote cell division in plant roots and shoots. However, their targets, biological functions, and implications in mammalian systems have rarely been examined. In this study, we show that one cytokinin, zeatin riboside, can prevent pheochromocytoma (PC12) cells from serum deprivation-induced apoptosis by acting on the adenosine A2A receptor (A2A-R), which was blocked by an A2A-R antagonist and a protein kinase A (PKA) inhibitor, demonstrating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 56 publications
2
25
0
Order By: Relevance
“…Thus, CGS rescues the corticostriatal synaptic disconnection and progressive motor impairment observed in HD mice (15,50). These findings together with several earlier reports suggest that activation of the A 2A R, a cAMP-elevating receptor, is a therapeutic option in HD and elicits beneficial effects on several key HD symptoms (including formation of intranuclear inclusions, impaired motor coordination, brain atrophy, and urea cycle deficiency) (15,(52)(53)(54). Consistent with the possible beneficial role of the A 2A R in HD, Mievis and colleagues demonstrated that elimination of the A 2A R exacerbated HD progression in a mouse model of HD (55).…”
Section: Figsupporting
confidence: 63%
“…Thus, CGS rescues the corticostriatal synaptic disconnection and progressive motor impairment observed in HD mice (15,50). These findings together with several earlier reports suggest that activation of the A 2A R, a cAMP-elevating receptor, is a therapeutic option in HD and elicits beneficial effects on several key HD symptoms (including formation of intranuclear inclusions, impaired motor coordination, brain atrophy, and urea cycle deficiency) (15,(52)(53)(54). Consistent with the possible beneficial role of the A 2A R in HD, Mievis and colleagues demonstrated that elimination of the A 2A R exacerbated HD progression in a mouse model of HD (55).…”
Section: Figsupporting
confidence: 63%
“…In fact, aiming at a treatment against familial dysautonomia, kinetin has been applied to patients at a dose of 23.5 mg/Kg/d for 28 d with promising results [9, 33]. The exogenous application of CKs and their anti-ageing effects for fibroblast cells [3436], and the interaction between CKs and the adenosine A2A-receptor and its function as novel neuroprotectant [35] and anti-inflammatory [37] agent with immune suppressive effects have interesting immunomodulatory implications for human cells. Quite intriguingly and apart from the external application/addition of CKs to mammalian cells a recent finding on the regulation of LOG-like protein (CK-activating enzyme) by the animal pathogen M .…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4] Interestingly, the cytokinin zeatin riboside has been shown to activate adenosine A 2A receptor signaling in a mammalian neuronal cell line. 5 Although the expression of the Gs-coupled A 2A R varies widely by mammalian cell type, it is known to be broadly expressed by immune system cells, with the activation of the A 2A R playing a role in terminating inflammation via the regulation of cells involved in innate and adaptive immunity. 6 Given the adenosine-based structure of zeatin riboside, its activity as an A 2A R agonist is not entirely surprising; however, it does endow the compound with significant therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%